The Two Faces of SLA: Mental Representation and Skill - Van Patten, Bill (International Journal of English Studies, 2010)
In this essay, I argue for viewing mental representation and skill as distinct components of language acquisition. My claim is that language is not a monolithic entity—not a new concept, but one that is often overlooked by instructors and some scholars. I examine language as being (minimally) composed of mental representation and skill. Representation refers to the abstract and implicit knowledge that underlies all language. Skill refers to the use of language, especially fluency (the intersection of speed and accuracy). By thinking about language as at least the distinction between representation and skill, we might better sort out some of the issues related to adult SLA, namely the role that instruction has, and what instruction can actually impact.